Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1016/j.ijid.2019.04.011
|View full text |Cite
|
Sign up to set email alerts
|

First outbreak of Oropouche Fever reported in a non-endemic western region of the Peruvian Amazon: Molecular diagnosis and clinical characteristics

Abstract: Introduction: Oropouche fever is an under-reported and emerging infectious disease caused by Oropouche virus (OROV). Its incidence is under-estimated mainly due to clinical similarities with other endemic arboviral diseases and the lack of specific diagnostic tests. We report the first outbreak of Oropouche fever in a western region of the Peruvian Amazon in Huanuco, Peru. Methods: A transversal study was carried out during an outbreak in the western Region of Huanuco, Peru between January and July of 2016. Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 21 publications
0
28
0
1
Order By: Relevance
“…Amplification by PCR assay for the detection of OROV was carried out using the primers described by Moreli et al [14], and PCR conditions described by Silva-Caso et al [9].…”
Section: Molecular Detection Of Orov Denv Chikv and Zikvmentioning
confidence: 99%
See 1 more Smart Citation
“…Amplification by PCR assay for the detection of OROV was carried out using the primers described by Moreli et al [14], and PCR conditions described by Silva-Caso et al [9].…”
Section: Molecular Detection Of Orov Denv Chikv and Zikvmentioning
confidence: 99%
“…In Peru situation is similar, studies have reported the presence of the four serotypes of DENV in the Peruvian coast, being the serotype DENV 2 the most frequent during the period from May to August (i.e., in 2016), as well as the Zika virus (ZIKV) and the Chikungunya virus (CHIKV) [7]. In the last 3 years, the presence of the Oropouche virus (OROV) has been reported, reemerging in some areas such as Madre de Dios or recently appearing in other areas such as Huánuco [8,9]. Our study describes the presence of OROV, an emerging pathogenic arbovirus in the north coast of Peru and its main clinical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In Peru, the increasing prevalence of DENV has caused different outbreaks, reaching up to 35,000 confirmed cases per year, and largely affecting the southern region of Cajamarca [ 12 ]. However, in recent years other emerging viral pathogens have gained attention due to their increasing detection in Peru and Latin America, such as Zika, Chikungunya and Oropuche virus, with epidemiological implications still unknown in our population [ 4 , 7 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, Semliki group alphaviruses have been implicated in causing arthralgias [15] and persistent incapacitating joint pain due to MAYV infection has been previously reported in a series of imported cases [16][17][18]. Accurate clinical differentiation between arbovirus and MAYV is a challenge for clinicians in endemic areas [21]; however, without sensitive and speci c diagnostic tools, a precise etiological diagnosis cannot be easily achieved [14,22].…”
Section: Introductionmentioning
confidence: 99%